Physical assurance for electronic devices and systems - Rahman, Mir Tanjidur; Tehranipoor, Mohammad H. (Springer, 2021)
This book provides readers with a comprehensive introduction to physical inspection-based approaches for electronics security. The authors explain the principles of physical inspection techniques including invasive, non-invasive and semi-invasive approaches and how they can be used for hardware assurance, from IC to PCB level. Coverage includes a wide variety of topics, from failure analysis and imaging, to testing, machine learning and automation, reverse engineering and attacks, and countermeasures. Provides the first book in the area of physical inspection and assurance for electronics security; Describes opportunities for unique countermeasures, including physical assurance and inspection of electronics, as well as physical fingerprinting based on analog parameters; Enables and categorizes a range of approaches to hardware security.